Pengaruh Fear Of Missing Out dan Online Customer Experience terhadap Keputusan Pembelian Skincare Scarlett(Studi Pada Generasi Z Pengguna Produk Skincare Scarlett di Yogyakarta) - Alfat Alfat; Heri Prasetyo (CV Muara Edukasi, 2026)
This study aims to analyze the influence of Fear of Missing Out (FoMO) and Online Customer Experienceon the Purchasing Decision of Scarlett skincare products among Generation Z in the Special Region of Yogyakarta. The increasing use of social media and the rapid development of e-commerce have changed consumer behavior, particularly among Generation Z, in making skincare purchasing decisions. This study employed a quantitative approach using a survey method. The population consisted of Generation Z consumers in the Special Region of Yogyakarta who had purchased Scarlett skincare products online. The sampling technique used was purposive sampling, with a total of 150 respondents. Data were collected through questionnaires using a five-point Likert scale and analyzed using multiple linear regression analysis with IBM SPSS Statistics version 26. The hypotheses were tested using validity, reliability, classical assumption, t-test, F-test, and coefficient of determination (R²) analyses. The results indicate that Fear of Missing Out (FoMO) has a positive and significant effect on the Purchasing Decision of Scarlett skincare products, with a regression coefficient of 0.483, a t-value of 4.368, and a significance value of 0.000 < 0.05. Online Customer Experiencealso has a positive and significant effect on Purchasing Decision, with a regression coefficient of 0.563, a t-value of 5.901, and a significance value of 0.000 < 0.05. Simultaneously, Fear of Missing Out (FoMO) and Online Customer Experiencehave a positive and significant effect on the Purchasing Decision of Scarlett skincare products among Generation Z in the Special Region of Yogyakarta, as indicated by an F-value of 226.335 and a significance value of 0.000 < 0.05. The Adjusted R Square value of 0.752 indicates that 75.2% of the variance in Purchasing Decision can be explained by Fear of Missing Out (FoMO) and Online Customer Experience, while the remaining 24.8% is explained by other variables not included in this study